The Impact of Toxic Cadmium Chloride on the Hematological Parameters in Fresh Water Fish Cyprinus carpio (Linnaeus) - Metigouda, Shivraj (International Journal of Pharmaceutical & Biological Archive, 2016)
In this present experiment the toxicity of fish Cyprinus carpio were exposed in both lethal and sublethal concentration of Cadmium Chloride for (24h, 48h, 72h & 96 hours) were exposed. The acute toxicity (LC50) of Cadmium Chloride was found to be 14 mg/L. One fifth (1/5th, i.e. 2.8 mg/L) of the acute toxicity value was selected as the sub lethal concentration for sub acute test. The present investigation was carried out to study the impact of toxic Cadmium Chloride on the haematological parameters in fresh water fish Cyprinus carpio in both lethal (1, 2, 3, and 4 days) and sub lethal (1, 5, 10, and 15 days) concentration. The blood parameters like Red blood corpuscle (RBC), white blood corpuscle (WBC), Haemoglobin (Hb), Packed cell volume (PCV), Mean corpuscular volume (MCV), Mean corpuscular haemoglobin (MCH) and Mean corpuscular haemoglobin concentration (MCHC) are commonly studied in fishes to assess the impact of Cadmium Chloride in aquatic biota. In Red blood corpuscle at lethal concentration maximum reduction of -65.397% was observed on day 4 and in White blood corpuscle the Maximum count 10.610 x 103 was observed on day 1 under lethal concentration, which later regressed on 2nd, 3rd and 4th day. The anaemia produced due to Cadmium Chloride treatment might be the reasons for the decrease in the RBC count, haemoglobin percentage and haematocrit value at lethal concentration, which therefore clearly suggests the species response to Cadmium Chloride.